ANALISIS PENETAPAN KEWARISAN MAFQUD PADA PUTUSAN NOMOR 318/Pdt.P/2022/PA.Kab.Mn - Alifia Farhanah; Muhammad Muhammad (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
This research analyzes the determination of inheritance in mafqud cases based on Decision No. 318/Pdt.P/2022/PA.Kab.Mn. This research aims to evaluate the legal basis and considerations of judges in determining the status of death of individuals with mafqud status, as well as its implications for the distribution of inheritance. The research uses a literature method with a normative approach, utilizing secondary data in the form of legal documents, laws and regulations, and related literature studies. The results show that Islamic inheritance law and the Civil Code have differences in determining the period of mafqud until the status of death can be determined. Based on the judge's consideration, the determination of the death of a mafqud individual is carried out by referring to the general phenomenon of human age and the doctrine of Islamic law which allows ijtihad for the sake of benefit. This study concludes that the judge's decision in this case is in line with the principles of Islamic inheritance law and applicable laws and regulations, providing legal certainty for the heirs in the distribution of inheritance.